Utility of unfractionated sodium heparin in the prevention of disseminated intravascular coagulation - Siqueira de Negreiros, Klender; Farias, Anibal Danilo (Salud Integral y Comunitaria, 2025)
Introduction: disseminated intravascular coagulation (DIC) is a serious disease characterized by a generalized activation of blood coagulation, with sequelae ranging from thrombus formation to severe bleeding. Objective: to analyze the fundamental alternatives for the management of DIC prevention related to the use of unfractionated heparin. Method: data collection was carried out through a search in the digital databases PUBMED, SCIELO (Scientific Electronic Library Online) and GOOGLE ACADEMIC. The articles were downloaded from the aforementioned platforms, and the Zotero system was used to make the corresponding citations and pertinent references. Results: according to the results achieved, the systematic review allowed to obtain a more detailed view of the studies arising from the data search, related to DIC and the use of unfractionated heparin in its prevention. The importance of research related to this drug was highlighted to improve the understanding and treatment of DIC with the aim of reducing its morbidity and mortality. Conclusions: despite unfractionated heparin presenting significant anticoagulant effects in its clinical utility, mainly in emergency situations due to its rapid action, there are few studies available for a better understanding of the management and functionality of UFH against DIC.